The sexuales of giant black bark aphid, Pterochloroides persicae (Hemiptera, Aphidoidea: Lachninae) - Wieczorek, Karina; Kanturski, Mariusz; Junkiert, Łukasz (Zootaxa, 2013)
The oviparous female and male of the giant black bark aphid Pterochloroides persicae (Cholodkovsky) are described and illustrated for the first time. Notes on distribution, biology and host plants are presented.